2011
DOI: 10.1007/s00415-010-5891-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fatigue 1 year after aneurysmal subarachnoid hemorrhage

Abstract: Fatigue is an important contributor to quality of life in patients who survive aneurysmal subarachnoid hemorrhage (SAH), but the determinants of this fatigue are unclear. We assessed the occurrence of fatigue 1 year after SAH and its relation to physical or cognitive impairment, passive coping, and emotional problems, measured 3 months after SAH. This was a prospective cohort study of 108 patients who visited our SAH outpatient clinic 3 months after SAH and who were living independently in the community 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 18 publications
(21 reference statements)
3
79
0
3
Order By: Relevance
“…In addition, baseline depression scores were associated with high fatigue scores at follow-up. This is in line with a previous longitudinal study that suggested that baseline depression was associated with long-term fatigue [10]. …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, baseline depression scores were associated with high fatigue scores at follow-up. This is in line with a previous longitudinal study that suggested that baseline depression was associated with long-term fatigue [10]. …”
Section: Discussionsupporting
confidence: 80%
“…Longitudinal studies found evidence that early PSD was associated with long-term PSF [10, 11], and long-term PSD was also associated with long-term PSF [7]. Early depressive symptoms correlated positively with both early fatigue and long-term fatigue, but no long-term depression data were available [12].…”
Section: Introductionmentioning
confidence: 99%
“…This reduction has been reported to remain stable at 6 month-follow-up producing an overall better functional health status, characterized by fewer symptoms of depression, and improvements in both sleep and physical endurance [44]. …”
Section: Treatmentmentioning
confidence: 99%
“…Cognitive impairment has been found to worsen fatigue after subarachnoid haemorrhage [44,45] and brain injuries; nonetheless, this association has received little attention. Additionally, in a sub-study on quality of life of the International Stroke trial, Mead and colleagues found that a worse mental health score and worse emotional role function measured with SF-36 and increasing age were significantly associated with fatigue [23].…”
Section: Predisposing and Associated Factorsmentioning
confidence: 99%
“…[22]. Fatigue is often underdiagnosed in acute neurological treatment as it may become apparent only in complex, highly stimulating everyday life situations with numerous sources of distraction and multitasking [23]. Such a ‘holistic' perspective adequately captures how clinical neuropsychologists actually understand and treat brain diseases, instead of overemphasizing a lesion-deficit view [13].…”
Section: Are Brain Disorders Just Inside the Brain?mentioning
confidence: 99%